2016
DOI: 10.31018/jans.v8i3.949
|View full text |Cite
|
Sign up to set email alerts
|

Studies on influence of modified atmospheric storage conditions on biochemical parameters in pigeonpea seeds

Abstract: An experiment was conducted to study the influence of modified atmospheric storage conditions on biochemical parameters of pigeonpea seeds. The experiment was conducted at the Department of Seed Science and Technology, College of Agriculture, Raichur, Karnataka. The seeds are exposed to various gaseous combinationsand stored in 700 gauge polyethylene bag for ten months during July-2012 to April- 2013. The results revealed that, the seeds exposed to gaseous combination of 40% N2+00% O2+ 60% CO2 showed less redu… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
0
0
1

Year Published

2020
2020
2020
2020

Publication Types

Select...
2

Relationship

0
2

Authors

Journals

citations
Cited by 2 publications
(2 citation statements)
references
References 8 publications
0
0
0
1
Order By: Relevance
“…It should be noted that seed deterioration during storage could result in marked changes in the content and activity of enzymes capable for regarding the stored reserves (Prestley, 1986;Smith & Berjak, 1995;Walters, 1998) [40,41,42] . In the present investigation it was observed that the all biochemical activity in the seed was maximum due to, better maintenance of seed quality in modified atmospheric storage condition as compared to control (Vasudevan et al, 2014;Manjunatha et al, 2016;Feng et al, 1989) [28,43,44] .…”
Section: Effect Of Seed Treatment and Storage Condition On Seed Bioch...mentioning
confidence: 59%
“…It should be noted that seed deterioration during storage could result in marked changes in the content and activity of enzymes capable for regarding the stored reserves (Prestley, 1986;Smith & Berjak, 1995;Walters, 1998) [40,41,42] . In the present investigation it was observed that the all biochemical activity in the seed was maximum due to, better maintenance of seed quality in modified atmospheric storage condition as compared to control (Vasudevan et al, 2014;Manjunatha et al, 2016;Feng et al, 1989) [28,43,44] .…”
Section: Effect Of Seed Treatment and Storage Condition On Seed Bioch...mentioning
confidence: 59%
“…Hasil analisis regresi menunjukkan bahwa semakin lama periode penyimpanan benih, maka semakin tinggi daya hantar listrik (18,64 us/g/minggu), sebaliknya semakin menurun kecepatan tumbuh (0,89%/etmal/minggu), potensi tumbuh maksimum (9,46%/minggu), viabilitas (12,18%/minggu), dan panjang hipokotil (0,34cm/minggu) (Gambar 7). Meningkatnya daya hantar listrik, dan menurunnya kecepatan tumbuh, potensi tumbuh maksimum, dan viabilitas benih yang sejalan dengan semakin lamanya penyimpanan benih, sejalan dengan hasil penelitian lain yang dilakukan pada berbagai jenis benih rekalsitran seperti benih kakao, pinus Brasil, jabon putih, kacang gude, guanandi, kapas, tengkawang, kedelai, beberapa benih tanaman hutan tropis, trema, dan benih tanaman pupuk hijau "tare" (Baharudin, Ilyas, Suhartanto, & Purwantara, 2010;Araldi & Coelho, 2015;Yuniarti & Nurhasybi, 2015;Manjunatha, Vasudevan, Umesha, & Sravani, 2016;Nery, Prudente, Alvarenga, Paiva, & Nery, 2016;Oliveira et al, 2016;Rohandi & Widyani, 2016;Shibata & Coelho, 2016;Becerra-Vázquez, Sánchez-Nieto, Coates, Flores-Ortiz, & Orozco-Segovia, 2018;Yuniarti, Syamsuwida, & Kurniaty, 2018;Chandra, Sershen, Varghese, & Keshavkant, 2019;Mokhtari & Kizilsimsek, 2019).…”
Section: Number Of Leaves Length Of Epycotiyl and Hypocotyl And Numunclassified